Evaluating the Concept of Green Criminology: Pathways for Ensuring Environmental Justice in Bangladesh - Umma Habiba; Tanveer Ahmed (Dhaka University Law Journal, 2025)
By committing crimes against nature, we are effectively perpetrating ‘ecocide’. While there is a general awareness of the negative impact of environmental harm, the idea of “ecocide” within the field of criminology is rarely discussed. This study aims to introduce a green viewpoint for addressing environmental crimes. To date, the concept that environmental harm might be classified as a criminal act, with underlying socio-economic issues contributing to green crime, has not received the necessary level of attention. The paper explores the necessity of green criminology as a conceptual framework, the significance of discussing ‘green crime’ as a distinct concept within the field of criminology, the theoretical (criminological) perspectives that encompass green crimes, and how environmental justice can be achieved through the implementation of ‘green methods”. The researchers adopt an interdisciplinary approach since the article attempts to integrate the concepts of environmental harm and environmental crime to achieve environmental justice. Dhaka University Law Journal, 2025, 36 (1), 149-169